Sistematização metodológica para o auxílio no desenvolvimento de ônibus - Avila, Diego de (2014)
This work focuses on the concept of improving the development process of buses and also in enabling theoretical tools correlated to effectiveness. As a provision, it is apparent that there are a variety of methods and structures for their respective projects of various objectives, in some cases it may be difficult to interpret and thus making it unacceptable for industrial or media manager focusing is, therefore, in the systematization of methods such as guide elements for the understanding and proper management of data. Under the guidance of renowned authors, adopts a methodology related to systems engineering and suits the conditioning elements in a process of development facing the bus industry, thus developing a linear and organizational means to the procedural steps. Thus, it enables them to provide as a result a hierarchical system divided by modules related to the sectors of development, in order to facilitate the interpretation and the comprehensive management of the entire process, prompting closer, finally, the parallelism between the theory and the industrial environment. Still fostering, the modularization of the conceptual design process thus favoring the correlation between all stages of development, being exemplified in the application as a result of development of a concept of road buses. And in complement, can enable, in a qualitative form, the use of theoretical tools for the industry, which is believed to interfere directly in the reduction of cost, time-to-market and, among others, providing opportunities for competitive advantages.